Correction to: Self-care and remote care during pregnancy: a new paradigm? - A. Metin Gülmezoglu; Anne Ammerdorffer; Manjulaa Narasimhan; Alyce N. Wilson; Joshua P. Vogel; Lale Say; Özge Tunçalp (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.